Taxonomic and functional diversity along successional stages on post-coalmine spoil heaps - Bakr, Jawdat; Kompała-Bąba, Agnieszka; Bierza, Wojciech; Chmura, Damian; Hutniczak, Agnieszka; Błońska, Agnieszka; Nowak, Teresa; Magurno, Franco; Jagodziński, Andrzej M.; Woźniak, Gabriela (Frontiers in Environmental Science, 2024)
Coal is the most abundant fossil fuel in Europe, but the excavation of hard coal has covered large areas with disposed rock waste, and turned the natural habitats into disturbed novel ecosystems with harsh conditions differ in time and space. To examine the spontaneous complex successional gradient, we studied a large number of post coalmine heaps in Upper Silesia, which differ in vegetation type and age. Cluster analysis based on plant community composition (367 species in total) separated all surveyed plots on coal mining spoil heaps with herbaceous vegetation from Late Stage (LS) forests aged 14-56 years. Furthermore, the herbaceous vegetation was sub-grouped to three stages: Initial Stage (IS) aged 2-5 years, Early Stage (ES) aged 3-8 years and Mid-Stage (MS) aged 5-12 years. MS vegetation was characterised by the highest species richness and diversity (47 and 2.79) compared to ES (30 and 2.18) and IS (9 and 1.6), but higher species number and a similar diversity index occurred in LS (37 and 2.81). Functional diversity (FD) and community weighted mean (CWM) of nine functional traits showed higher (23.1) functional richness, higher (0.72) functional divergence, higher (4.5) functional dispersion, and higher value (24.4) of Rao's quadratic entropy in LS compared to those calculated from the first three stages. Species at the initial successional stage (IS) were characterised by lower canopy height, seed mass, higher lateral spread, and specific leaf area (SLA). Additionally, the lowest (0.22 mg CO2 per hour per square metre) soil respiration (Sr) rate was recorded from IS compared to (0.53, 0.82 and 1.00) from ES, LS and MS, respectively. The substrate water content (SWC) was the most important factor affecting the soil respiration, while the soil temperature (St) did not follow the well-studied relationship between soil respiration and soil temperature. Our spatial and temporal analyses illustrated changes in plant community assembly processes in the course of spontaneous vegetation succession on post coalmine spoil heaps. The importance of trait mediated abiotic filtration in community assembly in initial-, early-, and mid-stages of succession with an increase in competitive exclusion at the late successional stage was emphasized.